2022
DOI: 10.1111/jocn.16354
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of social media intervention in people with diabetes: An integrative review

Abstract: Aim This integrative review aimed to synthesise the available quantitative and qualitative studies on the effectiveness of diabetes self‐management education (DSME) delivered through social media on glycaemic control (HbA1c), knowledge, health‐related quality‐of‐life (HRQoL), anxiety, depression and self‐efficacy in people with diabetes mellitus. Background DSME is the main component of diabetes management which contributes to behavioural changes and the improvement of metabolic control and self‐monitoring ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Social media apps offer an innovative approach to overcoming barriers of traditional face-to-face delivery of DSMES, such as remote geographic locations, time constraints, or both (Davis et al, 2022). A 2022 study, found DSMES delivery via social media is an effective and accessible alternative for T2DM management (Yaagoob et al, 2022).…”
Section: Diabetes Self-management Education and Supportmentioning
confidence: 99%
“…Social media apps offer an innovative approach to overcoming barriers of traditional face-to-face delivery of DSMES, such as remote geographic locations, time constraints, or both (Davis et al, 2022). A 2022 study, found DSMES delivery via social media is an effective and accessible alternative for T2DM management (Yaagoob et al, 2022).…”
Section: Diabetes Self-management Education and Supportmentioning
confidence: 99%
“…Studies have shown that social media has an impact on people's health behaviors and decisions, not least in the wake of the COVID-19 pandemic [9,91]. There is also growing evidence that social media use among people with chronic conditions can lead to better clinical and psychosocial outcomes, as described in several reviews [8,[92][93][94]. Although some of these reviews call for more studies, their findings are promising.…”
Section: Comparison With Other Reviewsmentioning
confidence: 99%
“…New methods, such as mobile technology and social media, now complement traditional methods of recruiting study participants for public health interventions. [18][19][20][21][22][23] The COVID-19 pandemic has created an unprecedented demand for online solutions, including the recruitment of study participants. 24 25 Therefore, this study aimed to (1) analyse preferred sources of health information on diabetes prevention programmes and (2) identify sociodemographic determinants influencing these preferences among adults in Poland.…”
Section: Introductionmentioning
confidence: 99%